COVID-19: Individual freedom and herd culture - Briceño-León, Roberto (Gaceta Médica de Caracas, 2022)
Pharmaceutical and non-pharmaceutical measures recommended by health agencies to contain the COVID-19 pandemic are rejected by some citizens and political leaders and have been the subject of protests. The argument used is the defense of individual freedoms such as the right not to be vaccinated, wear a face mask, or respect quarantine. This article analyzes such actions from the perspective of negative liberty and counterposes the advantages of positive liberty, such as the self-imposition of restrictions in the interests of collective well-being.